Improving the Learning Ability of INC Practicum for Midwifery Students through Simple Phantom Learning Media - Rijanto Rijanto; Tatarini Ika Pipitcahyani; Ahdatul Islamiah (Alliance oh Health Activists (AloHA), 2021)
The role of the laboratory is very important in the development of science that is growing rapidly in universities today. Laboratories are also very much needed in order to meet the achievements of the vocational college curriculum which holds more practicum classes, one of which is Midwifery Education where 60% of the education curriculum is Practice. Practicum class is an important part of the curriculum because it can assess 3 (three) aspects, namely the psychomotor (skills), cognitive (knowledge), and affective (attitude) aspects of students. Practical learning aims to provide students with learning experience in applying theory as training material and preparation for clinical practice application, bringing students to the formation of attitudes, skills, ability to work together, and creativity in receiving knowledge. To support practicum learning in the laboratory, learning media in the form of phantoms are needed. It's just that the number of phantoms available in the laboratory is currently very limited and not in balance with the number of students, so that in carrying out practicum learning students are divided into several large groups and study alternately according to a predetermined schedule. Students can only do practicum learning in the laboratory because the phantom size does not allow it to be taken out of the laboratory room. Limited access of students to maximize practicum learning using these phantoms which is likely to result in not being optimal or students not mastering practicum skills. Keywords: INC practicum; simple phantoms; learning media